KUALITAS PELAYANAN ADMINISTRASI PEMASANGAN LISTRIK BARU PADA PT. PLN (PERSERO) AREA MAKASSAR SELATAN - Siswati Rachman (Universitas Muhammadiyah Makassar, 2020)
The purpose of this study is to determine the Quality of Administrative Services is applied in the Installation of New Electrical at PT. PLN (Persero) Area Makassar South. And find out the Constraints faced in providing Quality Administration Services Installation of New Electrical at PT. PLN (Persero) Area Makassar South. Type and design in this study uses descriptive quantitative, which describes the phenomenon of the quality of administrative services the installation of new electrical at PT. PLN (Persero) Area Makassar south. The results of the research show that the administrative Services are one of the types of services provided by PT.PLN (Persero) to the customer, which is of course a major concern of the company to maintain the company's image in the eyes of customers. Administrative services provided include administrative services the installation of new electrical, the addition of electrical power and electrical connections while. The whole of the process of providing administrative services, which allow contact Between customers and employees more and more, so that the administrative services rendered vulnerable to the complaint given to the customer due to dissatisfaction with the service provided. Customer dissatisfaction with the services provided, the course will have an adverse impact on the company. Therefore, to avoid such things, then the company should provide quality service. The indicators used to measure service quality are tangible, Reliability, Responsiveness, Assurance, Empathy